An analysis of the German perfekt - Klein, Wolfgang (Language, 2000)
The German Perfekt has two quite different temporal readings, as illustrated by the two possible continuations of the sentence Peter hat gearbeitet in i, ii, respectively: (i) Peter hat gearbeitet und ist müde. Peter has worked and is tired. (ii) Peter hat gearbeitet und wollte nicht gestört werden. Peter has worked and wanted not to be disturbed. The first reading essentially corresponds to the English present perfect; the second can take a temporal adverbial with past time reference ('yesterday at five', 'when the phone rang', and so on), and an English translation would require a past tense ('Peter worked/was working'). This article shows that the Perfekt has a uniform temporal meaning that results systematically from the interaction of its three components-finiteness marking, auxiliary and past participle-and that the two readings are the consequence of a structural ambiguity. This analysis also predicts the properties of other participle constructions, in particular the passive in German.